Evaluating the effectiveness of alternative treatments for menopausal symptoms in postmenopausal women - S V Yureneva; E I Ermakova (IP Berlin A.V., 2017)
Purpose of the study - to evaluate the effectiveness of black cohosh extract (Chi-Klim drug) and its combination with beta-alanine (Chi-Klim Alanine) for the treatment of menopausal symptoms in women in the early and late postmenopausal women. Materials and methods. A pilot randomized clinical trial included 60 patients aged 40 to 65 years with a duration of menopause not less than 12 months and with a frequency of vasomotor manifestations (tidal) not less than 10 per day. The study did not include women who received menopausal hormone therapy or alternative methods of therapy for the past 3 months. Results. The therapy there was a significant reduction in the severity of menopausal manifestations in both treatment groups, however, in the group 2 the decline was more effective. Acceptance of the drug based on the extract of black cohosh in combination with a dietary supplement on the basis of beta-alanine was 2 times more effective than monotherapy with black cohosh reduced hot flushes per day and had a more pronounced adjoint positive effect on the psycho-emotional symptoms.